Effects of Rumen-Protected Creatine Pyruvate on Meat Quality, Hepatic Gluconeogenesis, and Muscle Energy Metabolism of Long-Distance Transported Beef Cattle - Lu, Guwei; Li, Yanjiao; Mao, Kang; Zang, Yitian; Zhao, Xianghui; Qiu, Qinghua; Qu, Mingren; Ouyang, Kehui (Frontiers in Animal Science, 2022)
Pre-slaughter long-distance transport resulted in a rapid depletion of muscle glycogen and lead to a higher rate of dark, firm and dry (DFD) meat. Therefore, enhancing muscle glycogen reserves is critical for beef cattle prior to transportation. Creatine pyruvate (CrPyr) can provide simultaneous pyruvate and creatine, are both proven to promote the glycogen reserves. This study aimed to investigate the effects of transport treatment and dietary supplymentation of rumen-protected (RP)-CrPyr on the meat quality, muscle energy metabolism, and hepatic gluconeogenesis of beef cattle. Twenty 18 months-old male Simmental crossbred cattle (659 ± 16 kg) were allotted to 4 treatments based on a 2 × 2 factorial arrangement with two RP-CrPyr levels (140 g/d or 0 g/d) and two transport treatments (12 h or 5 min): ST_CrPyr0, ST_CrPyr140, LT_CrPyr0 and LT_CrPyr140. Three cattle per group were slaughtered after 30 days of feeding. The interaction of transport and RP-CrPyr had a significant effect on the muscle pH45 min, redness, glycogen content, GP, and AMP level (P < 0.05). Compared with short-distance transport, long-distance transport increased the muscle pH45 min value, redness, yellowness, drip loss, and creatine level (P < 0.05), decreased muscle glycogen content and glycolytic potential (GP), and liver glucose amount (P < 0.05). Supplementation of RP-CrPyr decreased the activities of creatine kinase and lactate dehydrogenase in serum, muscle pH24 h value, redness, yellowness, lactate content, AMP level, and AMP/ATP (P < 0.05), increased the muscle glycogen content, GP, hexokinase activity, ATP and ADP levels, and ATP/ADP, liver pyruvate and glucose contents, activity of pyruvate carboxylase in the liver of cattle than those in the nonsupplemented treatments (P < 0.05). These results indicated that dietary RP-CrPyr supplementation might be favorable to improve meat quality and regulatory capacity of energy metabolism of beef cattle suffered long-distance transport followed with recovery treatment, by increasing muscle glycogen storage and energy supply and hepatic gluconeogenesis.